Fintech companies: taxonomy of services and development of innovations (on the example of Kaspi bank JSC) (Journal of Economic Research & Business Administration, 2023)
The financial sector of the Republic of Kazakhstan is facing a radical transformation. Using digital technologies to offer innovative services, new innovative developments are emerging in areas such as asset management, lending or insurance. Despite the growth in investment, there are very few theoretical ideas in the phenomenon of fintech companies. Until now, the proposals of fintech companies have been mainly studied from a functional point of view. Since the functional point of view is not enough to fully understand the proposals of fintech companies, a classification of non-functional characteristics is proposed. Therefore, the analysis of FinTech companies in the consumer-oriented sector is limited. The taxonomy proposed in this study includes 11 dimensions structured by common interactions with prospects, data, and revenue generation. On this basis, this taxonomy contributes to descriptive knowledge about fintech companies, allowing researchers and practitioners to analyze the service offerings of fintech startups and organizations in Kazakhstan in a structured way. At the same time, the impact of innovative products on the activities of Kaspi Bank JSC and its financial results is shown.